2011
DOI: 10.3390/nu3020228
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rotavirus Infectivity by a Neoglycolipid Receptor Mimetic

Abstract: Group A rotaviruses are a major cause of diarrhea in the young of many mammalian species. In rotavirus infected piglets mortality can be as high as 60%. Previous research in this laboratory has identified a porcine intestinal GM3 ganglioside receptor that is required for sialic acid-dependent rotavirus recognition of host cells. In addition, we previously demonstrated exogenously added GM3 can competitively inhibit porcine rotavirus binding and infectivity of host cells in vitro. Sialyllactose, the carbohydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…These results are in agreement with previous studies showing that the infectivity of SA-dependent strains of RV was reduced in the presence of SA-containing compounds ( 31 , 32 ) . Bergner et al ( 33 ) reported that a sialyllactose-containing neoglycolipid reduced RV OSU strain binding to MA-104 cells and in newborn piglets. Similarly, sialyloligosaccharides isolated from egg yolk hindered the infectivity of a SA-dependent strain of RV isolated from simians (SA-11), both in vitro and in vivo ( 34 ) .…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with previous studies showing that the infectivity of SA-dependent strains of RV was reduced in the presence of SA-containing compounds ( 31 , 32 ) . Bergner et al ( 33 ) reported that a sialyllactose-containing neoglycolipid reduced RV OSU strain binding to MA-104 cells and in newborn piglets. Similarly, sialyloligosaccharides isolated from egg yolk hindered the infectivity of a SA-dependent strain of RV isolated from simians (SA-11), both in vitro and in vivo ( 34 ) .…”
Section: Discussionmentioning
confidence: 99%
“…HMO are resistant to host hydrolases, and .90% of HMO are undigested and arrive intact in the large intestine (5). HMO have been shown to modulate proliferation, differentiation, and apoptosis of intestinal cells in vitro (6,7) and act as decoys to prevent adherence of pathogens to host epithelial cells (8,9). Another contribution of HMO to intestinal health is in its prebiotic effect on infant gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Colostrum and milk from cattle and other species naturally contain a variety of OS, but the biological functions of these have yet to be completely determined . Some milk OS have been shown to bind to bacterial exotoxins and pathogens including Campylobacter jejuni , pathogenic E. coli , and rotavirus . Oligosaccharides from bovine milk have been shown to have strong affinity for several enteropathogenic strains of Escherichia coli isolated from dairy calves .…”
Section: Discussionmentioning
confidence: 99%
“…17,35-41 Some milk OS have been shown to bind to bacterial exotoxins and pathogens including Campylobacter jejuni, pathogenic E. coli, and rotavirus. 39,[42][43][44][45][46] Oligosaccharides from bovine milk have been shown to have strong affinity for several enteropathogenic strains of Escherichia coli isolated from dairy calves. 43 These findings have led some to hypothesize that mammarysecreted OS are a component of lactogenic immunity and function to help protect the neonate from pathogens and bacterial translocation while the gut is open.…”
Section: Discussionmentioning
confidence: 99%